Precipitation in Al-Li-Si ternary alloys - YAMAMOTO, Atsushi; TANIBUCHI, Yuji; NOZATO, Ryoichi; TSUBAKINO, Harushige; SAKAI, Ryutaro (Journal of Japan Institute of Light Metals, 1993)
Precipitation behavior of Al-2.0mass%Li-0.2mass%Si and Al-0.8mass%Li-0.5mass%Si ternary alloys has been investigated mainly by means of micro-Vickers hardness measurements and transmission electron microscopy. Aging treatments were performed at constant temperatures in the range of 328 to 573K. Age hardening occurs at all temperatures. The precipitation of both the δ' (Al3Li) phase and fine equilibrium (AlLiSi: T) phase contributes to the hardness increase. The shape of the T phase is rod-like at the early stage of aging and changes to plate-like with prolonged aging time. The orientation relationship between the matrix (α) and T phase is as follows: (001)α//(110)T, [100]α//[001]T.